Pattern analysis of S. haematobium infection and elimination in the area of Alsuki, Sudan - Abdelshafie, Rawia A.; Abdalla Mohamed, Abdalla I. (International Journal Of Community Medicine And Public Health, 2021)
Background: The aim of this study was to determine the current conditions of children of the selected area, for the purpose of measuring the new effective health program for schistosomiasis disease eliminations and obtain the prevalence intensity and risk factors of S. haematobium among school children in the study area. Methods: A descriptive cross-sectional study was used to screen school going children of all the ages from five randomly selected schools from Alsuki region. A statistical analysis derived from data formulated based on 1062 samples aged between 6 and 15 years attending the selected schools during the period testing within 6 months were enrolled. Results: The impact of health awareness program was measured usefully and the responded factor for reducing the Schistosomiasis diseases was significantly became less than (0.05). Therefore, the actual qualified fitting degree and applicability was significantly becoming (p value=0.001). Conclusions: This research concluded that the prediction of Schistosomiasis diseases due to the risk Ratio of the collected data for those who did not attended awareness over the people who attended program became (0.248).